Pengaruh Sosialisasi, Tarif, Sistem E-Filing Terhadap Kepatuhan Wajib Pajak Dengan Program Pps Sebagai Variabel Pemoderasi - Harryanto Harryanto; Estralita Trisnawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This study examines tax socialization, tax rates, and the application of the e-filing system to measure taxpayer compliance. The PPS program is also a moderating variable in this study's analysis regarding the correlation between tax socialization and taxpayer compliance, tax rates and compliance, and the introduction of e-filing systems and compliance. Quantitative technique approach is used in this study. Research data obtained from primary sources in the form of filling out questionnaires given to respondents. A total of 200 samples were used in this study using purposive sampling based on the answers from the questionnaire. Structural equation model (SEM) is used for hypothesis testing. Based on research findings, tax socialization has a small impact on the level of taxpayer compliance, but the impact of tax rates and the e-filing system is quite large. Furthermore, PPS programs can have a sizeable impact on tax rates when used as a moderating variable. The PPS variable has a small impact on taxpayer compliance, apart from socialization and installation of the e-filing system. This analysis shows the need for the Indonesian Tax Directorate to redouble its efforts to improve tax compliance.